Identifikasi Peran Keluarga Penderita dalam Upaya Penanganan Gangguan Jiwa Skizofrenia - Rosdiana Rosdiana (Media Kesehatan Masyarakat Indonesia, 2018)
Schizophrenia is a description of the syndrome with a variety of causes and course of the disease are widespread,as well as some of the consequences that depend on the balance of genetic and socio-cultural influences.This study aims to identify the role of families of patients in Handling People with schizophrenia. Qualitative researchmethod with phenomenology approach through interviews, observation and documentation to 6 informants.The results showed that families are able to make the right decisions and take advantage of the health facility bydelivering the patient to the health center or hospital even though it was quite far away, but the family has a wrongassumption, that the hospital where care is good for patients, so the lack of family support when patients run theprogram in a mental hospital. Family didn’t know the different causes, symptoms and since when the patient beginsto experience schizophrenia, the families also do not know how to treat and modify the environment to be able tosupport the recovery people with of schizophrenia. The conclusion of this study are the ignorance of the family inproviding support while the person running the program in a psychiatric hospital, ignorance family in the know,understand, maintain and modify the environment that leads to relapse, even worse schizophrenias experienced bypatients in Sebakung Jaya Health Center.